Two‐Dimensional MXene‐Polymer Heterostructure with Ordered In‐Plane Mesochannels for High‐Performance Capacitive Deionization. Issue 51 (8th November 2021) - Li, Qian; Xu, Xingtao; Guo, Jingru; Hill, Jonathan P.; Xu, Haishan; Xiang, Luoxing; Li, Chen; Yamauchi, Yusuke; Mai, Yiyong
Abstract: The application of traditional electrode materials for high‐performance capacitive deionization (CDI) has been persistently limited by their low charge‐storage capacities, excessive co‐ion expulsion and slow salt removal rates. Here we report a bottom‐up approach to the preparation of a two‐dimensional (2D) Ti3 C2 T x MXene‐polydopamine heterostructure having ordered in‐plane mesochannels (denoted as mPDA/MXene). Interfacial self‐assembly of mesoporous polydopamine (mPDA) monolayers on MXene nanosheets leads to the mPDA/MXene heterostructure, which exhibits several unique features: (1) MXene undergoes reversible ion intercalation/deintercalation and possesses high conductivity; (2) mPDA layers establish redox capacitive characteristics and Na + selectivity, and also help to prevent self‐stacking and oxidation of MXene; (3) in‐plane mesochannels enable the smooth transport of ions at the internal spaces of this stacked 2D material. When applied as an electrode material for CDI, mPDA/MXene nanosheets exhibit top‐level CDI performance and cycling stability compared to those of the so far reported 2D materials. Our study opens an avenue for the rational construction of MXene‐organic hybrid heterostructures, and further motivates the development of high‐performance CDI electrode materials. Abstract : This communication reports a bottom‐up approach to a two‐dimensional (2D) Ti3 C2 T x MXene‐polydopamine heterostructure with ordered in‐plane cylindrical mesochannels. The resultant 2D heterostructure shows top‐level CDI performance in its application as electrode material for capacitive deionization.